Thermally controlled droplet formation in flow focusing geometry : formation regimes and effect of nanoparticle suspension - Murshed, S. M. Sohel (2012)
This paper reports experimental investigations on the droplet formation of deionized water and a nanofluid in a heat-induced microfluidic flow focusing device. Besides the effect of temperature, the effects of nanoparticle suspension (nanofluid) and the flow rate of aqueous fluid on the droplet formation and size manipulation were studied. At constant flow rates of the two liquids, three different droplet breakup regimes were observed and their transition capillary numbers as well as temperatures were identified. The heat generated by an integrated microheater changes the droplet formation process. Increasing the temperature enlarges the size of the droplets significantly. These results also demonstrate that the titanium oxide (15 nm)/deionized water-based nanofluid exhibits similar characteristics in droplet formation at different temperatures and any small change in the flow rate of this nanofluid has little impact on the size of the droplets formed in a flow focusing geometry.